Diagnostic Performance of Fractional Flow Reserve From CT Coronary Angiography With Analytical Method - Zhang, Jun-Mei; Han, Huan; Tan, Ru-San; Chai, Ping; Fam, Jiang Ming; Teo, Lynette; Chin, Chee Yang; Ong, Ching Ching; Low, Ris; Chandola, Gaurav; Leng, Shuang; Huang, Weimin; et al. (Frontiers in cardiovascular medicine, 2021)
The aim of this study was to evaluate a new analytical method for calculating non-invasive fractional flow reserve (FFR AM ) to diagnose ischemic coronary lesions. Patients with suspected or known coronary artery disease (CAD) who underwent computed tomography coronary angiography (CTCA) and invasive coronary angiography (ICA) with FFR measurements from two sites were prospectively recruited. Obstructive CAD was defined as diameter stenosis (DS) ≥50% on CTCA or ICA. FFR AM was derived from CTCA images and anatomical features using analytical method and was compared with computational fluid dynamics (CFD)-based FFR (FFR B ) and invasive ICA-based FFR. FFR AM , FFR B , and invasive FFR ≤ 0.80 defined ischemia. A total of 108 participants (mean age 60, range: 30–83 years, 75% men) with 169 stenosed coronary arteries were analyzed. The per-vessel accuracy, sensitivity, specificity, and positive predictive and negative predictive values were, respectively, 81, 75, 86, 81, and 82% for FFR AM and 87, 88, 86, 83, and 90% for FFR B . The area under the receiver operating characteristics curve for FFR AM (0.89 and 0.87) and FFR B (0.90 and 0.86) were higher than both CTCA- and ICA-derived DS (all p < 0.0001) on per-vessel and per-patient bases for discriminating ischemic lesions. The computational time for FFR AM was much shorter than FFR B (2.2 ± 0.9 min vs . 48 ± 36 min, excluding image acquisition and segmentation). FFR AM calculated from a novel and expeditious non-CFD approach possesses a comparable diagnostic performance to CFD-derived FFR B , with a significantly shorter computational time.